(untitled) - Lofts, Norh (Garden City, New York, 1970)
Norah Lofts, renowned as a bestselling novelist and storyteller, shows in this novel that she possesses a remarkable talent for suspense. Here is the romantic chiller at its finest, a stunning and engrossing work full of terrifying twists and suprises, quite literally from the first page to the last sentence. A Fawcett Crest book.
Keywords: American literature; 20th century